Etika Kerja dan Kepuasan Pasien: Studi Empiris pada Rumah Sakit UNIMUS Semarang - Rahman, Arif; Sikki, Nurhaeni; Triani Putri, Melati; Fadill Akbar, Muhammad; Ayu Renatasari, Distya; Tsani Putri, Meitri; Dina, Soneta; Agung Prabowo, Hanif; Choiri Rohmawan, Hanung (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study seeks to investigate the correlation between the work ethics of healthcare personnel and patient satisfaction at UNIMUS Hospital in Semarang, Indonesia. Data were gathered using a qualitative methodology through comprehensive interviews with ten informants, comprising five healthcare professionals and five outpatient patients. The results indicate that ethical principles, including empathy, honesty, fairness, and professional accountability, significantly influence patients' favorable evaluations of healthcare services. Patients indicated increased satisfaction while receiving treatment characterized by respect, compassion, and transparent communication. Nonetheless, upholding ethical consistency poses a problem, particularly in the context of elevated workloads and administrative pressures. The research underscores the necessity for a cohesive ethical management framework that incorporates continuous training and performance assessment centered on ethical conduct. These findings advance the establishment of patient-centered healthcare practices rooted in professional ethics. In conclusion, work ethics should be regarded not merely as a moral duty but also as a strategic component in improving patient satisfaction and institutional trust in healthcare services.